Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 137973 by mnjuly1970 last updated on 08/Apr/21

                       .......Advanced ... ... ... ... Calculus.......      prove that:::          𝛗=∫_0 ^( 1) ((ln(1βˆ’x))/(1+x^2 ))dx=(Ο€/8)ln(2)βˆ’G ...βœ“      where  G is catalan number...

.......Advanced............Calculus.......provethat:::Ο•=∫01ln(1βˆ’x)1+x2dx=Ο€8ln(2)βˆ’G...βœ“whereGiscatalannumber...

Answered by EnterUsername last updated on 08/Apr/21

∫_0 ^1 ((ln(1βˆ’x))/(1+x^2 ))dx=∫_0 ^(Ο€/4) ln(1βˆ’tanΞΈ)dΞΈ  =∫_0 ^(Ο€/4) ln(cosxβˆ’sinx)dxβˆ’βˆ«_0 ^(Ο€/4) lncosxdx  =∫_0 ^(Ο€/4) ln[(√2)cos(x+(Ο€/4))]dxβˆ’((G/2)βˆ’((Ο€ln2)/4))  =(Ο€/8)ln2+∫_0 ^(Ο€/4) ln(sinx)dxβˆ’((G/2)βˆ’((Ο€ln2)/4))  =(Ο€/8)ln2βˆ’(G/2)βˆ’((Ο€ln2)/4)βˆ’((G/2)βˆ’((Ο€ln2)/4))=(Ο€/8)ln2βˆ’G

∫01ln(1βˆ’x)1+x2dx=∫0Ο€4ln(1βˆ’tanΞΈ)dΞΈ=∫0Ο€4ln(cosxβˆ’sinx)dxβˆ’βˆ«0Ο€4lncosxdx=∫0Ο€4ln[2cos(x+Ο€4)]dxβˆ’(G2βˆ’Ο€ln24)=Ο€8ln2+∫0Ο€4ln(sinx)dxβˆ’(G2βˆ’Ο€ln24)=Ο€8ln2βˆ’G2βˆ’Ο€ln24βˆ’(G2βˆ’Ο€ln24)=Ο€8ln2βˆ’G

Commented by mnjuly1970 last updated on 08/Apr/21

 grateful...

grateful...

Answered by mathmax by abdo last updated on 09/Apr/21

f(a)=∫_0 ^1  ((ln(1+ax))/(1+x^2 ))dx β‡’f^β€² (a)=∫_0 ^1  (x/((ax+1)(x^2  +1)))dx  =(1/a)∫_0 ^1  ((ax+1βˆ’1)/((ax+1)(x^2  +1)))dx =(1/a)[arctanx]_0 ^1 βˆ’(1/a)∫_0 ^1  (dx/((ax+1)(x^2  +1)))  =(Ο€/(4a))βˆ’(1/a)∫_0 ^1  (dx/((ax+1)(x^2  +1)))  let decompose F(x)=(1/((ax+1)(x^2  +1)))  F(x)=(Ξ±/(ax+1)) +((mx+n)/(x^2  +1))  Ξ±=(1/((1/a^2 )+1)) =(a^2 /(1+a^2 ))  lim_(xβ†’+∞) xF(x)=0=(Ξ±/a) +m β‡’m=βˆ’(a/(1+a^2 ))  F(o)=1=Ξ±+n β‡’n=1βˆ’(a^2 /(1+a^2 ))=(1/(1+a^2 )) β‡’F(x)=(a^2 /((a^2  +1)(ax+1)))  +((βˆ’(a/(a^2  +1))x+(1/(1+a^2 )))/(x^2  +1)) β‡’βˆ«_0 ^1  F(x)dx=(a^2 /(a^2  +1))∫_0 ^1  (dx/(ax+1))  βˆ’(1/(a^2  +1))∫_0 ^1  ((axβˆ’1)/(x^2  +1))dx =(a/(a^2  +1))[ln(ax+1)]_0 ^1 βˆ’(a/(2(a^2  +1)))∫_0 ^1  ((2x)/(x^2  +1))dx  +(Ο€/(4(a^2  +1)))=((aln(a+1))/(a^2  +1)) βˆ’(a/(2(a^2  +1)))ln(2)+(Ο€/(4(a^2  +1))) β‡’  f^β€² (a)=(Ο€/(4a))βˆ’((ln(a+1))/(a^2  +1))+((ln2)/(2(a^2  +1))) βˆ’(Ο€/(4a(a^2  +1)))  =(Ο€/(4a))(1βˆ’(1/(a^2 +1)))βˆ’((ln(a+1))/(a^2  +1))+((ln2)/(2(a^2  +1))) =((Ο€a)/4)βˆ’((ln(a+1))/(a^2  +1))+((ln2)/(2(a^2  +1)))  β‡’βˆ«_0 ^1  f^β€² (a)da =(Ο€/4)∫_0 ^1  ada βˆ’βˆ«_0 ^1  ((ln(a+1))/(a^2  +1))da+((ln2)/2)∫_0 ^1  (da/(a^2  +1))  =(Ο€/4)Γ—(1/2) βˆ’βˆ«_0 ^1  ((ln(1+x))/(x^2  +1))dx +((ln2)/2).(Ο€/4)  =(Ο€/8)βˆ’βˆ«_0 ^1  ((ln(1+x))/(x^2  +1))dx+(Ο€/8)ln2  =f(1)=∫_0 ^1  ((ln(1+x))/(1+x^2 ))dx β‡’  2∫_0 ^1  ((ln(1+x))/(x^2  +1))dx =(Ο€/8)+(Ο€/8)ln2 β‡’βˆ«_0 ^1  ((ln(1+x))/(x^2  +1))dx =(Ο€/(16))+(Ο€/(16))ln2  ?  if we want ∫_0 ^1  ((ln(1βˆ’x))/(x^2  +1))dx we use the parametric  f(a)=∫_0 ^1  ((ln(1βˆ’ax))/(x^2  +1))dx....be continued....

f(a)=∫01ln(1+ax)1+x2dxβ‡’fβ€²(a)=∫01x(ax+1)(x2+1)dx=1a∫01ax+1βˆ’1(ax+1)(x2+1)dx=1a[arctanx]01βˆ’1a∫01dx(ax+1)(x2+1)=Ο€4aβˆ’1a∫01dx(ax+1)(x2+1)letdecomposeF(x)=1(ax+1)(x2+1)F(x)=Ξ±ax+1+mx+nx2+1Ξ±=11a2+1=a21+a2limxβ†’+∞xF(x)=0=Ξ±a+mβ‡’m=βˆ’a1+a2F(o)=1=Ξ±+nβ‡’n=1βˆ’a21+a2=11+a2β‡’F(x)=a2(a2+1)(ax+1)+βˆ’aa2+1x+11+a2x2+1β‡’βˆ«01F(x)dx=a2a2+1∫01dxax+1βˆ’1a2+1∫01axβˆ’1x2+1dx=aa2+1[ln(ax+1)]01βˆ’a2(a2+1)∫012xx2+1dx+Ο€4(a2+1)=aln(a+1)a2+1βˆ’a2(a2+1)ln(2)+Ο€4(a2+1)β‡’fβ€²(a)=Ο€4aβˆ’ln(a+1)a2+1+ln22(a2+1)βˆ’Ο€4a(a2+1)=Ο€4a(1βˆ’1a2+1)βˆ’ln(a+1)a2+1+ln22(a2+1)=Ο€a4βˆ’ln(a+1)a2+1+ln22(a2+1)β‡’βˆ«01fβ€²(a)da=Ο€4∫01adaβˆ’βˆ«01ln(a+1)a2+1da+ln22∫01daa2+1=Ο€4Γ—12βˆ’βˆ«01ln(1+x)x2+1dx+ln22.Ο€4=Ο€8βˆ’βˆ«01ln(1+x)x2+1dx+Ο€8ln2=f(1)=∫01ln(1+x)1+x2dxβ‡’2∫01ln(1+x)x2+1dx=Ο€8+Ο€8ln2β‡’βˆ«01ln(1+x)x2+1dx=Ο€16+Ο€16ln2?ifwewant∫01ln(1βˆ’x)x2+1dxweusetheparametricf(a)=∫01ln(1βˆ’ax)x2+1dx....becontinued....

Terms of Service

Privacy Policy

Contact: info@tinkutara.com